Analisis Strategi Pemasaran Pembiayaan Murabahah Pada Produk KPR Hijrah Dalam Meningkatkan Jumlah Nasabah - Sari, Reni Ilma; Anggraini, Tuti; Irham, Mawaddah (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2024)
Hijrah products in increasing the number of customers. The method used in this study is a descriptive qualitative method. Data collection techniques used by observation, interviews and documents related to the study, then the data is classified according to the topic of the problem discussed. This study reveals events or phenomena that occurred when the research took place at Bank Muamalat KCP Stabat. The results of this study indicate that the marketing strategy for KPR Hijrah products at Bank Muamalat KCP Stabat is in accordance with the aspects that have been determined by Bank Muamalat KCP Stabat such as segmentation, targeting and positioning. Where in this marketing strategy,the KPR product, price, promotion, place, person, physical evidence to influence consumer decisions to buy and use the products and services offered. As for the murabahah financing agreement for KPR Hijrah home ownership at Bank Muamalat KCP Stabat, it really helps the community in choosing KPR Hijrah products at Bank Muamalat KCP Stabat.